Pengembangan Aplikasi Pelelangan Ternak Burung Lovebird berbasis Android - Khrisna Indrawan Eka Putra; Nurudin Santoso; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Online auction is an auction method that can be accessed online. Auction is a method of making a sale by bidding with an increasing value in accordance with the provisions of the price provided by the auctioneer. In the lovebird bird lovers community, there is still no integrated system in terms of management and selling for owned birds. To solve this problem, an auction system is developed. This auction system provides a feature to view the ongoing auction list and detailed information on the auction such as birds being sold, information about the time and number of recent bids, comments on ongoing auctions and bidding history list at the auction, making auctions directly, a list of transactions that must be met as well as information on auctions that the user has. This system was developed on the android platform using the Kotlin programming language where the data retrieval process will make requests on available servers by using GraphQL queries to facilitate the process of retrieving data on the server more easy. This system has been tested using white-box testing on unit testing and integration and black-box testing in validation testing. In addition, usability testing is done by using the System Usability Scale method with the final score being 82,5 so that the system can be categorized as acceptable.